RETRACTED: Regression model of students subjective well-being learning at technical universities - Biktemirova E. I.; Shagiakhmetova E. I.; Guryanova O.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001